Use of Cost-effective Vacuum-assisted Closure Technique for Shell Fracture Repair and Coelomic Cavity Rupture Healing in a Chelonia carbonaria - Monteiro, Louysse Helene; da Silva, Sandy Kelly Souza Marques; Benarrós, Marina Sette Camara; Lopes, Cinthia Távora de Albuquerque; Domingues, Sheyla Farhayldes Souza (Acta Scientiae Veterinariae, 2021)
Background: The vacuum-assisted closure (VAC) therapy system has been used as a noninvasive wound management technique for shell damage in Chelonians. These animals are excellent candidates for VAC therapy because of their unique shell anatomyconsists of dermal bones, which make bandage placement easier. Beyond that, they are suited for this technique behaviorally, because they are not inclined to remove the vacuum system intentionally. Considering the possibility of Testudines shell repair with the use of less invasive techniques that result in additional dermal bone lesions, the objective of the present study is to describe the adaptation of a vacuum dressing protocol using low-cost and easily accessible materials for post-traumatic shell healing of a specimen of Chelonoidis carbonaria. Case: A specimen of tortoise (Chelonoidis carbonaria), a male, weighing 630 g, approximately 3-year-old, was received at the Veterinary Hospital - Wild Animals Sector in the Federal University of Pará (UFPA) because of being run over by a vehicle. On physical examination, fractures of the dermal plaques and underlying bone structures were found, with rupture of the coelomic cavity. In addition, there was exposure and incarceration of an intestinal loop, with the presence of bleeding. According to the findings of the physical screening examination, the patient's prognosis was defined as good, as described in the literature that specifically focused on chelonian shell injuries. The animal was sent to the diagnostic imaging sector. Then, drug therapy was provided for pain control, vitamins were administered for nutritional support, and antibiotics and anti-inflammatory drugs were instituted. For the closure of the shell and coelomic cavity, a bandage was used with the VAC therapy system adapted as described for Chelonians in previous reports. After a complete osteosynthesis and closure of the coelomic cavity, repair of the integumentary component of the shell was possible. For this procedure, the animal did not need to be anesthetized. The patient was physically restrained by being placed in suspension on a support with a diameter smaller than the plastron. Complete asepsis of the shell was necessary. On top of the lesion, a polypropylene mesh and color less dental resin were applied. The animal continued to be evaluated after the repair to check for potential complications. This procedure ensured that the repaired plates remained stable. Furthermore, the animal did not seem to have any discomfort with the resin when moving, so the animal was discharged after 25 days of hospitalization. Discussion: Radiography was important to determine the condition of the animal and clinical prognosis, and thus, to perform the proper treatment. The VAC therapy system was successful in assisting the patient's recovery. It enabled the reduction of the healing time since shell injuries usually require four to eighteen months to heal. In this report, the healing process only required 17 days, demonstrating that the VAC therapy system is a beneficial treatment to treat traumatic injuries in Testudines. The restoration protocol of the integumentary component using dental resin is less invasive, and this type of material has been used previously by other authors. Drug treatment with aminoglycosides and sulphonamides administered prophylactically has proven to be effective and has been used successfully in reptiles. These drugs may be combined with maintenance fluid therapy to prevent adverse reactions from aminoglycosides, such as nephrotoxicity. It was concluded that the use of the VAC therapy system reduced the time of post-traumatic healing of the carapace and proved to be an innovative approach to treat traumatic injuries in Testudines in a less invasive way.